Automated Intrusion Monitoring System - Mohamad Asrul, Ahmad Siaman (UTeM, 2009)
The aim of this project is to design and build a prototype of an automated parking system which will automatically park and retrieve the vehicle without the driver. The driver will park his vehicle on a pallet at the platform of the car park. Then the sensor will detect the available empty parking spaces and display them on the control panel. After the driver selects the desired parking space on the control panel, the vehicle will be transported to that parking space. In order to retrieve the vehicle, the driver will select the location of his vehicle on the control panel. The system will retrieve the vehicle from the parking space and send it back to the original position where the driver is waiting. Programmable Logic Controller (PLC) will be used in the design of the prototype of the automated parking system. The PLC is used to control the movement needed to transport and retrieve the vehicle to and from the available parking space based on the signal from the driver. A program needs to be created for the PLC using CX-Programmer by drawing ladder diagram. Power window motor and direct current (DC) motor would be used to provide movements to transport the vehicle in the parking system. Besides that, limit switch will act as sensor to detect the available parking space and also the location of the carrier.